Low-dose versus standard-dose alteplase in acute ischemic stroke in Asian stroke registries: an individual patient data pooling study. Issue 7 (October 2019) - Wang, Xia; Li, Jingwei; Moullaali, Tom J; Lee, Keon-Joo; Kim, Beom Joon; Bae, Hee-Joon; Wang, Anxin; Wang, Yilong; Wang, David Z; Wang, Yongjun; Kumamoto, Masaya; Toyoda, Kazunori; et al.
Objective: To investigate the comparative efficacy and safety of the low-dose versus standard-dose alteplase using real-world acute stroke registry data from Asian countries. Methods: Individual participant data were obtained from nine acute stroke registries from China, Japan, Philippines, Singapore, South Korea, and Taiwan between 2005 and 2018. Inverse probability of treatment weight was used to remove baseline imbalances between those receiving low-dose versus standard-dose alteplase. The primary outcome was death or disability defined by modified Rankin Scale scores of 2 to 6 at 90 days. Secondary outcomes were symptomatic intracerebral hemorrhage and death. Generalized linear mixed models with the individual registry as a random intercept were performed to determine associations of treatment with low-dose alteplase and outcomes. Results: Of the 6250 patients (mean age 66 years, 36% women) included in these analyses, 1610 (24%) were treated with low-dose intravenous alteplase. Clinical outcomes for low-dose alteplase were not significantly different to those for standard-dose alteplase, adjusted odds ratios for death or disability: 1.00 (0.85–1.19) and symptomatic intracerebral hemorrhage 0.87 (0.63–1.19), except for lower death with borderline significance, 0.77 (0.59–1.01). Conclusions: The present analyses of real-world Asian acute stroke registry data suggest that low-dose intravenous alteplase has overall comparable efficacy for functional recovery and greater potential safety in terms of reduced mortality, to standard-dose alteplase for the treatment of acute ischemic stroke.